2023
DOI: 10.1029/2023ms003765
|View full text |Cite
|
Sign up to set email alerts
|

Convection and Convective‐Organization in Hothouse Climates

Guy Dagan,
Jacob T. Seeley,
Nathan Steiger

Abstract: In a “hothouse” climate, warm temperatures lead to a high tropospheric water vapor concentration. Sufficiently high water vapor levels lead to the closing of the water vapor infrared window, which prevents radiative cooling of the lower troposphere. Because water vapor also weakly absorbs solar radiation, hothouse climates feature radiative heating of the lower troposphere. In recent work, this radiative heating was shown to trigger a shift into a novel “episodic deluge” precipitation regime, where rainfall oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…( C ) ExoCAM experiments with increasing CO 2 concentration for an aqua-planet with modern solar constant ( 49 ). ( D ) Small-domain fixed-SST (sea surface temperature) cloud-resolving experiments using DAM ( 22 ) and SAM ( 45 ). Blue and red lines show results with the solar spectrum (blue) and an M star spectrum (red) in ( 22 ), and the purple line depicts results from ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( C ) ExoCAM experiments with increasing CO 2 concentration for an aqua-planet with modern solar constant ( 49 ). ( D ) Small-domain fixed-SST (sea surface temperature) cloud-resolving experiments using DAM ( 22 ) and SAM ( 45 ). Blue and red lines show results with the solar spectrum (blue) and an M star spectrum (red) in ( 22 ), and the purple line depicts results from ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides mean precipitation, precipitation variability should also change in hot climates, as suggested in (22,(44)(45)(46)(47). The temporal pattern of precipitation in hothouse climates may transform from quasi-steady to organized episodic deluges, with outbursts of short and heavy rain alternating with several-day dry spells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the fact that we use small domain simulations, the absence of largescale circulation effects and the use of a fixed SST in our simulations should be considered as potential limitations in the scope of our results. These factors warrant further investigation and may refine our understanding of the relationship between absorbing aerosols and extreme precipitation (e.g., see Dagan et al (2023) for large domain simulations of hothouse climate episodic deluges regime). Furthermore, previous studies using global climate simulations (Dagan et al, 2021;Persad, 2023;Williams et al, 2023) demonstrated that the location of the absorbing aerosol perturbation matters for the local-and global-mean precipitation response.…”
Section: Discussionmentioning
confidence: 99%
“…In a seemingly unrelated context to absorbing aerosols, recent research has demonstrated that under hothouse climate conditions-warmer than our current climate, believed to have existed in the distant history of our planet -precipitation shifts from the quasi-equilibrium condition observed today to an "episodic deluge" regime. This regime is characterized by short and intense outbursts of rainfall separated by multi-day dry spells (Dagan et al, 2023;Seeley & Wordsworth, 2021;Song et al, 2023;Spaulding-Astudillo & Mitchell, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation